2022
DOI: 10.3390/molecules27217599
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antiproliferative Activity of Novel Neocryptolepine–Rhodanine Hybrids

Abstract: A series of novel neocryptolePine–rhodanine hybrids (9a,b, 11a–d, 14, and 16a,b) have been synthesized by combining neocryptolePine core 5 modified at the C-11 position with rhodanine condensed with the appropriate aryl/hetero aryl aldehydes. Based on these findings, the structures of the hybrids were confirmed by spectral analyses. By employing the MTT assay, all hybrids were tested for their in vitro antiproliferative activity against two cancer cell lines, including MDA-MB-231 (human breast) and HepG-2 (hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The Commercially available starting materials and solvents such as dimethyl formamide (DMF), and dimethyl sulfoxide (DMSO) were purchased from Sigma Aldrich and used as received without further purification. The key starting intermediate, 11-chloroneocryptolepine 1 was prepared according to our reported method [ 10 ]. Soluble starch was purchased from Doummar & Sons Co. Industrial City, Syria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Commercially available starting materials and solvents such as dimethyl formamide (DMF), and dimethyl sulfoxide (DMSO) were purchased from Sigma Aldrich and used as received without further purification. The key starting intermediate, 11-chloroneocryptolepine 1 was prepared according to our reported method [ 10 ]. Soluble starch was purchased from Doummar & Sons Co. Industrial City, Syria.…”
Section: Methodsmentioning
confidence: 99%
“…In last decades, nature is fruitful and active area for many pharmaceutical compounds encouraging researchers to discover and develop compounds to reach the best and optimum activity against several diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodanine and its derivatives have been widely studied as a potential anti-tumour agent due to its medical properties [ [97] , [98] , [99] ], however, PR has participated in a limited number of cancer-related research. A series of neocryptolepine–rhodanine hybrids was formed and tested as an anticancer drug [ 100 ]. The MTT assay showed that most of the formed hybrids had effective cytotoxicity on the tumour cell line hepatocellular carcinoma (HepG-2), similar to the standard drug 5-fluorouracil (5-FU).…”
Section: Biological Application Of Prmentioning
confidence: 99%
“…Eggers et al studied the toxicity of rhodanine on kidney cells of monkeys, his results demonstrated that rhodanine had no toxic effect at a concentration of 150 μg/ml, but caused granulation of cells at a concentration of 200 μg/ml after a 4-day or longer exposure [ 119 ]. El-Bahnsawye et al evaluated a series of neocryptolepine (a natural plant extract) and rhodanine hybrids towards human breast (MDA-MB-231) and hepatocellular carcinoma (HepG-2) cancer cell lines [ 100 ]. In this research, they revealed that the tested hybrids showed strong selectivity for cancer cells over normal skin cell lines (BJ-1) at the maximum concentration.…”
Section: Properties Of Prmentioning
confidence: 99%